Projeto, construção e análise de desempenho de um forno solar alternativo tipo caixa a baixo custo - Melo, Aroldo Vieira de (2008)
An alternative box-type solar oven constructed from the scrap iron of a gas conventional cook is presented, which functions principles are the effect greenhouse and the concentration. The oven of the conventional cook is the baking enclosure where the absorber (pot) of the solar oven is located, being re-covered for a glass blade for the generation of the greenhouse effect isolated lateral and having deep its and for a composite the plaster base and EPS. Segments of plain mirrors had been placed in the laterals of the oven for the concentration of the radiation and a reflecting parabola was introduced in the baking enclosure for the exploitation of the incident reflected radiation in the interior of the oven. The oven is mobile to allow one better aiming of exactly in relation to the apparent movement of the sun. The thermal economic and of materials viabilities of the stove in study will be demonstrate The average internal temperature of the absorber was around 150°C and the internal temperature around 120°C. Will demonstrate that its low cost and good thermal performance represents basic characteristics for the viability of large use of such archetype, mainly for cooking the decreases and averages temperatures. One will reveal that the archetype in study is competitive with the box-type solar cooker conceived in the whole world